Numerical Investigation of the Influence of Roof Fracturing Angle on the Stability of Gob-Side Entry Subjected to Dynamic Loading - Zhibiao Guo; Lei Zhang; Zhibo Ma; Feixiang Zhong; Jingchao Yu; Siming Wang (Shock and Vibration)
In order to increase the mining rate of underground coal resources, an innovative nonpillar underground coal mining approach (fracturing roofs to maintain entry (FRME)) has been widely applied in China. The effect of roof fracturing determines whether the entry can be retained successfully or not. In this work, the tail entry of 21304 panel in Chengjiao Coal Mine (China) has been considered as the test site. The coal mine is located approximately 900 m underground. A numerical investigation on the relationship between the entry stability and roof fracturing angle was conducted. In order to investigate the reasonable scope of roof fracturing angle under static and dynamic loadings, the double-yield model was employed to simulate the gob materials, and the input parameters of the model were calibrated meticulously using the method of inversion analysis. Furthermore, dynamic loading was applied to research the influence of fracture of hard rock strata on the entry stability. The global model was validated with the field data. The simulation results demonstrate that the reasonable scope of the roof fracturing angle is 10–20°, in which case the distributions of vertical stress are favorable to the stability of gob-side entry. Additionally, the dynamic responses were found to be relatively moderate. The numerical method could provide a significant reference for the design of FRME approach.